Descentralização da atenção aos casos de tuberculose no município de João Pessoa do período de 2001 a 2009 - Pequeno, Gutenberg Alves (2011)
Tuberculosis TB is a public health problem that has being shown high rates of morbidity and mortality turning it into a priority among government health policies which establish guidelines and fix goals for its prevention and control. In Brazil, in 2003, a new decentralization strategy for TB control began to be defined: till that, cities became responsible for implementation of programs for TB control, incorporating actions at family health units. So, in João Pessoa, one of six priority cities for TB control in Paraiba, with characteristics and problems common to large urban centers, we sought to know whether decentralization of TB control, on the family health strategy field, has been consolidated in the city, and which factors influence users to elect the TB treatment location. Thus, this study aimed to assess the tendency of the proportion in tuberculosis cases reported in Primary Health Care in the city of João Pessoa, after ten years of implementation of the Directly Observed Treatment Short-course (DOTS). To this end, we chose to conduct a quantitative and qualitative research in the city of João Pessoa/PB/Brazil through a primary analytical ecological study of temporal series. In the quantitative research, data was collected in the Information System for Disease Notification database, and it involved all notification tuberculosis cases reported in the city including treatments performed in the period. In the analysis, we used the software for statistical analysis and charting R version 2.10.1, in what we assessed the proportions test and tendency of proportion test. In relation to qualitative data, it was obtained through interviews with 14 individuals in treatment, both in primary and in specialized health services, which were discussed based on Content Analysis and based in the literature on the subject. Results showed that there wasn´t significant statistical differences (p-value > 0,05) between the proportions of cases treated in primary care and that TB care in the city of João Pessoa remains centralized. Still, it was found in users' speech problems in the physical structure and functional as well as in the reference and counter-reference system. We concluded that for the decentralization process occurs effectively and efficiently, it is necessary not only to transfer the cases of TB for treatment completion in primary health care units, but also restructure services, improving the supply and quality of human resources and materials and to adapt the activities for the local reality.